(untitled) (Research, Society and Development, 2025)
This article addresses the theme of care, exploring different implications associated with the role of family caregivers of elderly individuals who have undergone lower limb amputation. Objective: To describe and analyze the repercussions of major lower limb amputation (MLLA) on family caregivers, identifying the main challenges they face and proposing intervention strategies to optimize the care process Methodology: A narrative literature review of a qualitative nature was conducted. The search encompassed databases such as PubMed, Scielo, Web of Science, PsycINFO, and Google Scholar, using keywords in Portuguese, English, and Spanish. The included studies were analyzed qualitatively to identify patterns and thematic categories. The heterogeneity of the studies was considered as a limitation. Concepts, data on the profile of these caregivers, as well as the psychological, physical, and social repercussions faced, difficulties in adapting to the new routine, and the impact on social and professional life will be presented. Results/Discussion: Elderly individuals with MLLA require continuous physical and emotional assistance, which is often provided by a family caregiver. The negative impacts on both the affected person and the caregiver are widely reported in the literature, as are the benefits of this experience, such as strengthening family ties, developing new skills, and personal growth. Final Considerations: Care requires a multidisciplinary, integrated, and continuous approach. To this end, it is necessary to implement support networks and strategies for the training and promotion of the well-being of caregivers in order to improve the quality of care provided.